Нечто из бездны: Повесть / Е. Артамонова - Артамонова Елена Вадимовна (Страшилки, 2006)
Экземпляры: (20170705) / Инвентарный номер: 31571 / Цена: 55.70 / Сис.шифр: Р2 / Авт.знак: А 86 / ГРНТИ: 17 / ББК: 84(2Рос=Рус)6